Comparative analysis of Hungarian Matricaria recutita (L.) Rausch. populations - Sztefanov, A.; Szabó, K.; Bernáth, J. (International Journal of Horticultural Science, 2003)
Matricaria recutita L. is a traditional medicinal plant in Hungary and its drug is known as „Hungaricum", world-wide. Plant samples and seeds were collected from 12 different habitats of three significant geographical regions of Hungary in 2001. Morphological, production biological and chemical properties of samples were examined. In relation to the morphological characteristics, a negative correlation (r= -0.75) could be observed between the average height of the plants (height of flowering shoots) and the pH value of the soil. According to the composition of the essential oil, the populations accumulating typically chamasulene (10-20%), a-bisabolol (30-50%) or bisabolol-oxid (30-50%) could be completely distinguished. Concerning the flavonoid composition the quantity of apigenin-7-glucoside was outstanding in the populations originating from the Great Hungarian Plain, it has reached the concentration of 1.8-2.8 mg/g, while the samples collected in Transdanubia could be characterised by much lower level of apigenin-7-glucoside (around 1.5 mg/g).